T-Cell-Driven Inflammation as a Mediator of the Gut-Brain Axis Involved in Parkinson's Disease - Campos-Acuña, Javier; Elgueta, Daniela; Pacheco, Rodrigo (Frontiers in Immunology, 2019)
Parkinson’s disease (PD) is a neurodegenerative disorder affecting mainly the dopaminergic neurons of the nigrostriatal pathway, a neuronal circuit involved in the control of movements, thereby the main manifestations correspond to motor impairments. The major molecular hallmark of this disease corresponds to the presence of pathological protein inclusions called Lewy bodies in the midbrain of patients, which have been extensively associated with neurotoxic effects. Importantly, different research groups have demonstrated that CD4+ T-cells infiltrate into the substantia nigra of PD patients and animal models. Moreover, several studies have consistently demonstrated that T-cell deficiency results in a strong attenuation of dopaminergic neurodegeneration in animal models of PD, thus indicating a key role of adaptive immunity in the neurodegenerative process. Recent evidence has shown that CD4+ T-cell response involved in PD patients is directed to oxidised forms of α-synuclein, one of the main constituents of Lewy bodies. On the other hand, most PD patients present a number of non-motor manifestations. Among non-motor manifestations, gastrointestinal dysfunctions result especially important as potential early biomarkers of PD, since they are ubiquitously found among confirmed patients and occur much earlier than motor symptoms. These gastrointestinal dysfunctions include constipation and inflammation of the gut mucosa and the most distinctive pathologic features associated are the loss of neurons of the enteric nervous system and the generation of Lewy bodies in the gut. Moreover, emerging evidence has recently shown a pivotal role of gut microbiota in triggering the development of PD in genetically predisposed individuals. Of note, PD has been positively correlated with inflammatory bowel diseases, a group of disorders involving a T-cell driven inflammation of gut mucosa, which is strongly dependent in the composition of gut microbiota. Here we raised the hypothesis that T-cell driven inflammation, which mediates dopaminergic neurodegeneration in PD, is triggered in the gut mucosa. Accordingly, we discuss how structural components of commensal bacteria or how different mediators produced by gut-microbiota, including short-chain fatty acids and dopamine, may affect the behaviour of T-cells, triggering the development of T-cell responses against Lewy bodies, initially confined to the gut mucosa but later extended to the brain.